2001
DOI: 10.1063/1.1345706
|View full text |Cite
|
Sign up to set email alerts
|

Role of parallel flow curvature on the mitigation of Rayleigh–Taylor instability

Abstract: The effect of a radially varying parallel equilibrium flow on the stability of the Rayleigh-Taylor ͑RT͒ mode is studied analytically in the presence of a sheared magnetic field. It is shown that the parallel flow curvature can completely stabilize the RT mode. The flow curvature also has a robust effect on the radial structure of the mode. Possible implications of these theoretical findings to recent experiments are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A general equation for the variation of the Þ -component of the fluid velocity along the fluid density gradient has been derived [see equation (13)]. For two distinct densities separated by a sharp boundary and for a continuously varying density, dispersion relations for the RT instability have been obtained and analyzed [see equations (18) and (38)]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A general equation for the variation of the Þ -component of the fluid velocity along the fluid density gradient has been derived [see equation (13)]. For two distinct densities separated by a sharp boundary and for a continuously varying density, dispersion relations for the RT instability have been obtained and analyzed [see equations (18) and (38)]. …”
Section: Resultsmentioning
confidence: 99%
“…Sarmah et al studied analytically the effect of a radially varying parallel equilibrium flow on the stability of the RT -mode in the presence of a sheared magnetic field [18]. It is found that the parallel flow curvature can completely stabilize the RT mode.…”
Section: Introductionmentioning
confidence: 97%